Pragmatic Considerations on Clinical Decision Support from the 2019 Literature - Duclos, C.; Bouaud, J.; Section Editors for the IMIA Yearbook Section on Decision Support (Yearbook of Medical Informatics, 2020)
Objectives: To summarize significant research contributions published in 2019 in the field of computerized clinical decision support and select the best papers for the Decision Support section of the International Medical Informatics Association (IMIA) Yearbook.Methods: Two bibliographic databases were searched for papers referring to clinical decision support systems (CDSSs) and computerized provider order entry (CPOE) systems. From search results, section editors established a list of candidate best papers, which were then peer-reviewed by external reviewers. The IMIA Yearbook editorial committee finally selected the best papers on the basis of all reviews including the section editors’ evaluation.Results: A total of 1,378 articles were retrieved. Fifteen best paper candidates were selected, the reviews of which resulted in the selection of three best papers. One paper reports on a guideline modeling approach based on clinical decision trees, both clinically interpretable and suitable for implementation in CDSSs. In another paper, authors promote the use of extended Timed Transition Diagrams in CDSSs to formalize consistently recurrent medical processes for chronic diseases management. The third paper proposes a conceptual framework and a grid for assessing the performance of predictive tools based on the critical appraisal of published evidence.Conclusions: As showed by the number and the variety of works related to decision support, research in the field is very active. This year’s selection highlighted pragmatic works that promote transparency and trust required by decision support tools.
Keywords: Medical informatics; International Medical Informatics Association; Yearbook; Decision Support Systems